Levantamento dos impactos ambientais dos parques eólicos na região da Costa Branca Potiguar - Fernandes, Bruna (Universidade Federal Rural do Semi-Árido, 2019)
The generation of wind energy has been highlighting a lot in the current scenario. Brazil is nowadays in the world production, and the state of greater prominence in production and installation potential is Rio Grande do Norte. A region that is currently being explored is a region of the Costa Blanca, Which is a clean and renewable energy, presents a series of environmental impacts, is dependent on the region's functionality, taking into account its flora and fauna, as well as social issues. This job moves your potential to the state of the state of the state of the species of the skylers against the state of the species. By conducting the survey, it is possible to list engineering solutions, to mitigate impacts around parks, and to improve the environment modified by developments in this sector.
Keywords: Areia Branca; Mata atlântica; Manguezal; Aves migratórias; Morcegos; White sand; Atlantic forest; Mangrove; Migratory birds; Bats; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA